Analisis Aspek Pasar dalam Pengembangan Bisnis di Era Digital - Amelia Husna; Nazryva Nur Muthia; Sri Rahayu Ningsih; Dini Vientiany (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
Market aspects analyze market potential, competition intensity, achievable market share, and marketing strategies that can be implemented to reach the desired market share. Through this analysis, business ideas can be effectively channeled to align with market needs and demands. The success of financial performance often depends on market and marketing capabilities, operations, accounting, human resources, and other functions. In the past, before marketing knowledge developed and became widely recognized as it is today, companies prioritized producing as much as possible before attempting to sell their products.In such circumstances, they ignored existing demand conditions, resulting in many producers experiencing failures and ongoing losses because production quantities did not align with market demand.